1994
DOI: 10.1080/00288233.1994.9513054
|View full text |Cite
|
Sign up to set email alerts
|

Some genetic factors affecting temperament inBos tauruscattle

Abstract: Temperament scores were recorded by two operators on a herd of Bos taurus beef cattle, including Angus and Hereford controls and various crossbred groups. The herd consisted of 765 cows, 653 calves at foot (average age 2 months), and 250 yearling heifers. Recording of temperament in the yards was carried out at weighing time in November 1982 using a 1-8 scale, and immediately afterwards when the herd was drafted for natural mating using a 1-6 scale, with higher scores indicating more difficulty experienced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
3
7

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 11 publications
7
31
3
7
Order By: Relevance
“…Regarding reactivity towards humans, our estimate (h 2 = 0.23) was in agreement with those found previously in dairy cattle [13,40,46], and beef cattle [27,31]. The heritability estimates found in the present study thus provide evidence in support of the possibility of selecting for emotional traits in sheep.…”
Section: Adjusted Means and P Values In Italicssupporting
confidence: 82%
See 1 more Smart Citation
“…Regarding reactivity towards humans, our estimate (h 2 = 0.23) was in agreement with those found previously in dairy cattle [13,40,46], and beef cattle [27,31]. The heritability estimates found in the present study thus provide evidence in support of the possibility of selecting for emotional traits in sheep.…”
Section: Adjusted Means and P Values In Italicssupporting
confidence: 82%
“…For instance, studies in sheep [26,37] and cattle [23,47] have shown that emotional reactivity differs between breeds. Nevertheless most studies on livestock concern reactivity to humans, whereas reactivity to novelty and to social isolation have not been accurately estimated [13,19,31,46]. In addition breed differences can be partly explained by non-genetic influences such as maternal effects, as extensively documented in rodents [38].…”
Section: Introductionmentioning
confidence: 99%
“…The fear tests used in the present study are related to human presence and social isolation from herd mates. Moderate to high correlations found between behavioral attributes show a common psychological base (Morris et al, 1994;King et al, 2006). Some others studies have revealed distinct reactions between genotypes, reporting for Bos indicus breeds or crossbreds greater agitation compared with Bos taurus (Grandin & Deesing, 1998;Barbosa-Silveira et al, 2006;Barbosa-Silveira et al, 2008a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Dairy cattle showed a higher approachability than beef cattle (Murphey et al, 1980) and were more reactive to sudden noises during cattle auctions (Lanier et al, 2000). Moreover, numerous behaviour studies were conducted for different beef breeds enabling a temperament ranking from more calm breeds like Herford and Angus to breeds that are more temperamental like German Simmental or Charolais (Morris et al, 1994;Gauly et al, 2002;Hoppe et al, 2010).…”
Section: Genetic Background Of Cattle Temperamentmentioning
confidence: 99%